Uji Efek Antibakteri Ekstrak Etanol Herba Seledri (Apium graveolens Linn.) Terhadap Escherichia coli dan Staphylococcus aureus dan Analisis KLT Bioautografi - Khildah Khaerati; Ihwan Ihwan (Biology Department, Mathematics and natural science, Tadulako University, 2011)
This research divided into two stage which are the inhibition growth capacity test using agar diffusion method with the incubator period 1 x 24 jam hours as the first stage and second stage testing the TLC-Bioautographic. Sample made with the concentration 0,5%, 1 %, 2% and 4% w/v. The capacity of growth inhibited showed on Staphylococcus aureus and than. The TLC-Bioautographic test to the chromatogram of fractionation result with Chloroform : Metanol (15 : 6) on Escherichia coli 1 active stains with Rf value 0,32, for Staphylococcus aureus resulted 2 active stains with Rf value in a row 0,88 and 0,32 Key words: Antibacteri, Apium graveolens, bioautographic.